2011
DOI: 10.1371/journal.pone.0022359
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Epimastigotes Are Able to Store and Mobilize High Amounts of Cholesterol in Reservosome Lipid Inclusions

Abstract: BackgroundReservosomes are lysosome-related organelles found in Trypanosoma cruzi epimastigotes. They represent the last step in epimastigote endocytic route, accumulating a set of proteins and enzymes related to protein digestion and lipid metabolism. The reservosome matrix contains planar membranes, vesicles and lipid inclusions. Some of the latter may assume rectangular or sword-shaped crystalloid forms surrounded by a phospholipid monolayer, resembling the cholesterol crystals in foam cells.Methodology/Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 56 publications
2
34
0
1
Order By: Relevance
“…Epimastigotes proliferate in the insect gut, a compartment full of blood meal. The parasite stores different nutrients, including heme [ 27 ] and lipids, such as cholesterol [ 28 ], in organelles derived from endosomes called reservosomes [ 29 ]. As nutrients become scarce, differentiation of epimastigotes into metacyclic-trypomastigotes is triggered and concomitantly these endosomes are consumed [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Epimastigotes proliferate in the insect gut, a compartment full of blood meal. The parasite stores different nutrients, including heme [ 27 ] and lipids, such as cholesterol [ 28 ], in organelles derived from endosomes called reservosomes [ 29 ]. As nutrients become scarce, differentiation of epimastigotes into metacyclic-trypomastigotes is triggered and concomitantly these endosomes are consumed [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been demonstrated that Leishmania parasites are able to acquire significant amounts of cholesterol from LDL particle endocytosis (Andrade‐Neto et al., ; De Cicco et al., ). This strategy has also been illustrated for other protozoan parasites such as Toxoplasma gondii , Trypanosoma cruzi , and Cryptosporidium parvum , which indicate that cholesterol is widely important for the intracellular survival and replication of pathogens (Coppens, Sinai, & Joiner, ; Ehrenman, Wanyiri, Bhat, Ward, & Coppens, ; Johndrow et al., ; Pereira et al., ; Portugal et al., ). Our experiments using LDL containing 3 H‐labeled cholesteryl linoleate suggest that Leishmania amastigote‐infected cells do not primarily increase the overall cellular uptake of cholesterol, but rather increased retention of cholesterol in the parasite‐containing subcellular fraction is observed when compared to a similarly prepared fraction containing latex beads.…”
Section: Discussionmentioning
confidence: 98%
“…The parasites were grown in Liver Infusion Tryptose (LIT) medium with 5% Neonatal Bovine Serum [13] at 28°C. Just before performing each experiment, parasites were counted in a Neubauer chamber and used when cultures were at exponential growth (usually 2-6x10 5 parasites/mL) [14]. …”
Section: Methodsmentioning
confidence: 99%